Improve network capacity on multi-hop 802.11-based wireless networks - Jabin, Niti; Sumaiya, Tasnuva (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.